Open DLT for Patient Privacy Protection in the Age of Healthcare Consumerism - Palombini, Maria; Shetty, Sachin; Harrell, PhD, Daniel (Blockchain in Healthcare Today, 2023)
Key discussion points of this panel session include: The role of open source DLTs in empowering and protecting patients data The role of where technical and data standards are pragmatically needed The technical and ethical considerations of patient data governance